PENGARUH METODE PERMAINAN BOARDGAME EDUCATION “PHARMAPOLEIN” TERHADAP PEMAHAMAN MATERI KEFARMASIAN MAHASISWA - Ilham Alifiar; Vidya Febrasca Tenderly; Annisa Nurhayati (JFL : Jurnal Farmasi Lampung, 2020)
ABSTRACT Mission of pharmacy education is to develop and nurture skills in lifelong learning. Broad insight, skills in communication, and teamwork is a must for the pharmaceutical profession. The learning method greatly affects the results of understanding each individual, especially in understanding pharmaceutical material which is considered difficult. Educational games are used as a teaching method because they help complement and strengthen the material being taught. Board games have continued to grow in popularity and the pedagogical value of the games has been supported many times. So, this board game is designed to have enough challenging elements to nurture student interest. The game tactic used collaboration and competition in the classroom. Competition has been found to increase motivation. Thus, that motivation can be used to understand the pharmaceutical material contained in the game. Aim this study is to determine the potential modification of the monopoly board game in increasing student comprehension of pharmaceutical material. The pharmapolein game was examined on both pharmacy and non-pharmacy student respondents (n = 12). From the test, it was obtained a correlation value of and 0.885 and a significance value of 0.000, so the conclusion was that the board game game could increase student knowledge in mastery of pharmaceutical science. Keywords: Board Games, Pharmapolein, Pharmacy